Comparative evaluation of the platelet-rich fibrin bandage versus gelatin sponge-assisted palatal wound healing of free gingival graft donor site: A case series - Samyak Gautam Belkhede; Sanjeev Kumar Salaria; Rajni Aggarwal (Wolters Kluwer Medknow Publications, 2019)
Periodontal plastic surgery often involves palatal donor site, thereby creating an open wound that is prone to postoperative complications such as bleeding, pain, and slow healing process. To prevent the same, platelet-rich fibrin (PRF) and gelatin sponge (GS) were utilized equally at the donor site in six patients. Patients were monitored at the 1st, 2nd, 3rd, and 4th weeks after surgery for postoperative discomfort (D), consumption of analgesics during first postoperative week, alteration of sensitivity (AS), change in feeding habits (CFH), complete wound epithelialization (CWE), and healing index (Landry et al. 1998). Two patients in the GS group showed significantly early CWE, higher healing index score, and less D, AS, and CFH postoperatively in comparison to the PRF group. It was suggested that GS can also be considered as an effective, economical, and biocompatible dressing material of choice to enhance wound healing and to minimize postoperative complications associated with the donor site.